Dynamic analysis of coupled train–track–bridge system subjected to debris flow impact. Issue 4 (March 2019) - Zhang, Xun; Wen, Zhipeng; Chen, Wensu; Wang, Xiyang; Zhu, Yan
With the increasing popularity of high-speed railway, more and more bridges are being constructed in Western China where debris flows are very common. A debris flow with moderate intensity may endanger a high-speed train traveling on a bridge, since its direct impact leads to adverse dynamic responses of the bridge and the track structure. In order to address this issue, a dynamic analysis model is established for studying vibrations of coupled train–track–bridge system subjected to debris flow impact, in which a model of debris flow impact load in time domain is proposed and applied on bridge piers as external excitation. In addition, a six-span simply supported box girder bridge is considered as a case study. The dynamic responses of the bridge and the running safety indices such as derailment factor, offload factor, and lateral wheel–rail force of the train are investigated. Some influencing factors are then discussed based on parametric studies. The results show that both bridge responses and running safety indices are greatly amplified due to debris flow impact loads as compared with that without debris flow impact. With respect to the debris flow impact load, the boulder collision has a more negative impact on the dynamic responses of the bridge and train than the dynamic slurry pressure. Both the debris flow impact intensity and train speed determine the running safety indices, and the debris flow occurrence time should be also carefully considered to investigate the worst scenario.